Profile of men's health in Malaysia: problems and challenges - Tong, S.F.; Low, W.Y.; Ng, C.J. (2011)
Men's health concerns have evolved from the traditional andrology and male sexual health to a more holistic approach that encompasses male psychological, social and physical health. The poor state of health in men compared to their female counterparts is well documented. A review of the epidemiological data from Malaysia noted a similar trend in which men die at higher rates in under 1 and above 15 years old groups and most disease categories compared to women. In Malaysia, the main causes of death in men are non-communicable diseases and injuries. Risk factors, such as risk-taking behaviour, smoking and hypertension, are prevalent and amenable to early interventions. Erectile dysfunction, premature ejaculation and prostate disorders are also prevalent. However, many of these morbidities go unreported and are not diagnosed early; therefore, opportunities for early intervention are missed. This reflects poor health knowledge and inadequate health-care utilisation among Malaysian men. Their health-seeking behaviour has been shown to be strongly influenced by family members and friends. However, more research is needed to identify men's unmet health-care needs and to develop optimal strategies for addressing them. Because the Malaysian population is aging and there is an increase in sedentary lifestyles, optimizing men's health will remain a challenge unless effective measures are implemented. The existing male-unfriendly health-care system and the negative influence of masculinity on men's health behaviour must be addressed. A national men's health policy based on a male-friendly approach to health-care delivery is urgently needed to provide a framework for addressing these challenges. Asian Journal of Andrology (2011) 13, 526-533; doi: 10.1038/aja.2010.125; published online 28 February 2011